An optimized HRM method for diagnosis of G6PD deficiency in kinh Vietnamese via viangchan mutation - Anh, Dang Thi Lan; Huong, Nguyen Thi Cam; Giang, Nguyen Dien Thanh; Hue, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
With Glucose-6-phosphate dehydrogenase (G6PD) deficiency being the most common enzyme disorder in human, there have been 184 discovered point mutations and several methods that have been applied for diagnosing this disease. However, these techniques often pose several major problems such as being time-consuming, low sensitivity and high cost. Recently, the High Resolution Melting (HRM) has been studied and proven to be effective for DNA genotyping, mutation scanning and sequence matching. Therefore, HRM has been chosen for diagnosing G6PD deficiency via Viangchan mutation in this study. In this study, a total of 56 dried blood spot samples (including six control samples which were known the exact genotype by sequencing and fifty unknown samples) were collected and extracted DNA by using QIAamp DNA Blood Mini Kit. Primers for HRM analysis were designed through by the Umelt software. Then HRM optimization was carried out for annealing temperature of primers (Ta) and MgCl2 concentration on six control samples. The optimized HRM protocol with 2.5 μM of MgCl2 and Ta at 62oC was applied for fifty G6PD samples and then comparing with ARMS-PCR genotyping results for the validation process. In the final step, genotyping results were confirmed by sequencing. In a results, both sensitivity and specificity of this technique reached 100%. Based on these favorable outcomes, this study has successfully optimized the HRM conditions for diagnosing fifty G6PD samples. It was such an essential precondition that showed HRM could be applied for other types of G6PD through other types of mutations such as Canton mutation or continues to be developed for HRM-Multiplex reactions.